Pigou, Taxation and Public Goods - Atkinson, A. B.; Stern, N. H. (Review of Economic Studies, 1974)
A. B. Atkinson, N. H. Stern; Pigou, Taxation and Public Goods12, The Review of Economic Studies, Volume 41, Issue 1, 1 January 1974, Pages 119–128, https://doi.